2017
DOI: 10.1002/macp.201700046
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polymerization of 2‐Hexyl[3]dendralene

Abstract: studies have reported the addition poly merization of [3]dendralene derivatives. [10] Previously, our group has reported the anionic polymerization of 2phenyl [3]den dralene (P3D) and 2(4methoxyphenyl) [3]dendralene (MP3D). [11] In both cases, anionic polymerization smoothly pro ceeds in polar solvents at low tempera ture, affording a polymer with a narrow mole cular weight distribution and a conjugate addition chain structure com prising conjugated carbon-carbon double bonds in the polymer chain, as shown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We presume that the nucleophilic addition of n -BuLi to either terminus of a 1,3-butadiene moiety of 1a generates the pentadienyl-lithium 7a or the phenylpropenyl-lithium 7b , which undergoes the nucleophilic substitution of bromobutane. Organolithium-initiated 1,4-addition polymerizations of dienes and dendralenes are known, but to our knowledge, 1,4-addition/substitution is without precedent for unsaturated hydrocarbons . Attempts to generalize this three-component, two C–C bond-forming process are underway.…”
mentioning
confidence: 99%
“…We presume that the nucleophilic addition of n -BuLi to either terminus of a 1,3-butadiene moiety of 1a generates the pentadienyl-lithium 7a or the phenylpropenyl-lithium 7b , which undergoes the nucleophilic substitution of bromobutane. Organolithium-initiated 1,4-addition polymerizations of dienes and dendralenes are known, but to our knowledge, 1,4-addition/substitution is without precedent for unsaturated hydrocarbons . Attempts to generalize this three-component, two C–C bond-forming process are underway.…”
mentioning
confidence: 99%
“…Many synthetic groups were focused on discovering and studying new vinyl monomers compatible with anionic polymerization, leading to the synthesis of novel materials with exciting properties. Ishizone’s and Ma’s , groups, reported the synthesis of several novel styrene and 1,3-diene derivatives bearing various substituents. For example, the anionic polymerization of styrene derivatives with bulky adamantyl groups generated well-defined polymers exhibiting higher T g values (>200 °C) than PS .…”
Section: Current Status Of Living Carbanionic Polymerizationmentioning
confidence: 99%
“…Since all dienyl structures can potentially undergo polymerization similar to 1,3-butadiene, a variety of microstructures can be formed in the resulting polymer. Earlier, we reported the successful polymerization of several 2-substituted [3]­dendralene derivatives (Figure c–e) to afford well-defined linear polymers with predictable molecular weights and narrow molecular-weight distributions using anionic initiators such as potassium naphthalenide (K-Naph) and sec -butyllithium ( s -BuLi). , In the case of poly­(P3D), two conjugate addition structures (1,4 and 4,6 structures) were observed, and their ratio was constant regardless of the polymerization conditions, while the vinyl addition structure was not detected. This indicated that the [3]­dendralene derivatives underwent conjugate addition during anionic polymerization and that the polymerizabilities of the two conjugated systems contained in P3D are similar to those in anionic polymerization.…”
Section: Introductionmentioning
confidence: 98%